Integrating subalterns into grand narratives in the God of Small Things - Nanthini Amathalingam (2010)
My aim in this essay is to re-iterate the subaltern stand, aided by Roy’s TGST that the story of the marginalised should be within the wider scope of grand narratives. Furthermore I will also establish in my stand that this importance cannot be achieved if it were to be completely detached from these grand narratives. Beginning with the title of the novel itself which empowers small things by establishing a god for them, I will move on to discuss the ways in which Velutha the ‘untouchable’ is given an importance as the god of small things. The empowerment of Velutha will be elaborated upon as a tragedy in his failure to transcendence the prejudice that surrounds ‘untouchables’. Unlike Subaltern Studies which states that the stories of the oppressed and marginalised should be recognised as multiple histories while refusing grand narratives as a whole, I will establish that the importance of these small histories cannot be achieved without being read within grand narratives. This will be examined through two main arguments which will conclusively state that the detachment of the subaltern from the context of the grand narrative is an idealistic state. The first of these arguments will state that grand narratives need to be acknowledged due to the basic fact that Subaltern Studies was established in order to refute the former. The second will state that the subaltern is indeed a creation of the caste system as a grand narrative thus stating that one cannot even begin to define the subaltern without the aid of the caste system. These two arguments will clearly state that the absolute refusal of grand narratives would result in a compromise of understanding the objective state of any situation and merely submerging representations within the subjective resulting from indulging entirely in small histories.